2006
DOI: 10.1590/s1519-69842006000300018
|View full text |Cite
|
Sign up to set email alerts
|

Gametogenesis and reproduction of the matrinxã Brycon orthotaenia (Günther, 1864) (Pisces: Characidae) in the São Francisco river, Minas Gerais, Brazil

Abstract: The gametogenesis and reproduction of the matrinxã, Brycon orthotaenia in the São Francisco river, Pirapora Region, Minas Gerais, were studied from December, 1998 to November, 1999. The matrinxã B. orthotaenia is an endemic species in the São Francisco river basin in Brazil and important for commercial fishing. The size of the 1 st gonadal maturation, indicated by the total length of the smallest spent males and spawned female, was 32.0 and 40.5 cm respectively. Reproduction occurred from October to January, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
27
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 9 publications
7
27
0
5
Order By: Relevance
“…The same relationship between the reproductive period and precipitation was observed for Salminus franciscanus Lima, Britski, 2007, for which the beginning of the reproductive period and an increase in the GSR occur in October, coinciding with the beginning of the rainy season in the São Francisco River Basin (Freitas et al, 2013). In the same watershed, Gonçalves et al (2006) also found that the reproductive period of the migratory fish B. orthotaenia occurs in the same period, between October and January. Salminus brasiliensis (cited as S. maxillosus) from the Upper Paraná River show a reproductive period between October and January (Vazzoler, 1996), similar to that observed for S. franciscanus from the São Francisco River (Freitas et al, 2013).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The same relationship between the reproductive period and precipitation was observed for Salminus franciscanus Lima, Britski, 2007, for which the beginning of the reproductive period and an increase in the GSR occur in October, coinciding with the beginning of the rainy season in the São Francisco River Basin (Freitas et al, 2013). In the same watershed, Gonçalves et al (2006) also found that the reproductive period of the migratory fish B. orthotaenia occurs in the same period, between October and January. Salminus brasiliensis (cited as S. maxillosus) from the Upper Paraná River show a reproductive period between October and January (Vazzoler, 1996), similar to that observed for S. franciscanus from the São Francisco River (Freitas et al, 2013).…”
Section: Discussionsupporting
confidence: 59%
“…In this way, as the condition factor of each fish is also affected by the gonad weight, the presence of individuals at different maturity stages in the same month can cause an increase in the monthly average dispersion of K values. When fish show a short reproductive period, as reported for S. brasiliensis in the Paraná River (Barbieri et al, 2001) and for matrinxã Brycon orthotaenia Günther, 1864 (Gonçalves et al, 2006), it is observed that the GSR increase is directly associated with the condition factor values. A similar situation occurs in fish with a marked seasonality in feeding rate, such as the tambaqui Colossoma macropomum (Cuvier, 1816) (Villacorta-Correa, Saint-Paul, 1999) and the pacu-toba Mylossoma cf.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Species in this genus are among the most threatened in Brazilian rivers and have been since the 1970s (Godoy, 1975). The matrinxã Brycon orthotaenia Günther, 1864, is a benthopelagic, predominantly herbivorous species endemic to the rio São Francisco basin which migrates during its reproductive period (Alvim & Peret, 2004;Gonçalves et al, 2006). Its body weight may reach more than 7 kg, thus it is a very important fish for commercial and sport fishing (Gonçalves et al, 2006).…”
mentioning
confidence: 99%
“…The matrinxã Brycon orthotaenia Günther, 1864, is a benthopelagic, predominantly herbivorous species endemic to the rio São Francisco basin which migrates during its reproductive period (Alvim & Peret, 2004;Gonçalves et al, 2006). Its body weight may reach more than 7 kg, thus it is a very important fish for commercial and sport fishing (Gonçalves et al, 2006). In riparian forests in the Neotropics, fruits and seeds is an essential part of the diet of adult Brycon species; and thus these fish play an important role in the dispersal of plants (Azevedo et al, 2011).…”
mentioning
confidence: 99%